Law, Empire, and the making of Roman estates in the provinces during the late republic - Eberle, L (University of Toronto Libraries, 2016)
This paper studies the implication of law in the Roman imperial project. It uses the creation of the legal framework for how Romans could acquire landholdings in the provinces of the Greek East in the second and first centuries BC as a case study in order to propose an alternative to the top-down/bottom-up dichotomy that characterizes prevailing approaches. By tracing the different legal arenas in which this framework was developed--Roman jurisprudence, provincial edicts, the senate in Rome--and the different social groups that participated in developing this framework in these arenas--Romans in the provinces, the members of Greek cities there, and Rome’s political elite--this study reveals law in the empire as a site of political debate, not between ruler and ruled, but between several competing groups that used law to shape and contest what the empire should mean for them.